Indicators of genomic evaluation of heifers using European criteria - Uskova, I.; Traisov, B.; Baimishev, M; Baimishev, K.; Vasilev, A. (International Scientific and Practical Conference on Agriculture and Food Security - Technology, Innovation, Markets, Human Resources (FIES nov. 13-14, 2019International Scientific and Practical Conference on Agriculture and Food Security - Technology, Innovation, Markets, Human Resources (FIES nov. 13-14, 2019, 2019)
The aim of the study is improvement of productive and reproductive indices of Holstein animals used in the Russian Federation due to their genomic evaluation using European criteria for this breed. The material for the research was repair heifers in the amount of 20 heads belonging to JSC "Niva" of the Stavropol region of Samara region. The genomic estimation of heifers was carried out in France in order to reveal the degree of the forecast' reliability of productive, reproductive qualities of heifers. The material for genomic evaluation was taken from the animal's auricle by puncture. The genomic evaluation revealed that not all heifers correspond to the expected characteristics of their parents' phenotypic features. The fat and protein content of the milk was positive for all heifers, while the milk content of 7 heifers was negatively correlated. According to the results of genomic evaluation, 3 heifers are classified as excellent, 3 as moderate and 4 as weak heifers. The conducted researches on genomic evaluation of heifers in "Niva" JSC indicate the prospects of its use in selection and breeding work, as further accelerated increase in the efficiency of dairy cattle breeding without the use of progressive methods of evaluation of repair young animals will not allow to increase the productive, native and qualitative parameters of dairy productivity of cows in a short period of time. At present 17 out of 20 genome-appraised heifers have confirmed the results of the conducted researches.Цель исследования - улучшение продуктивных и репродуктивных показателей животных голштинской породы, используемых в Российской Федерации, за счет их геномной оценки с использованием европейских критериев для этой породы. Материалом для исследования послужили ремонтные телки в количестве 20 голов, принадлежащие ОАО «Нива» Ставропольского края Самарской области. Геномная оценка телок проводилась во Франции с целью выявления степени достоверности прогноза продуктивных, репродуктивных качеств телок. Материал для геномной оценки брали из ушной раковины животного путем пункции. Геномная оценка показала, что не все телки соответствуют ожидаемым характеристикам фенотипических особенностей их родителей. Содержание жира и белка в молоке было положительным для всех телок, тогда как содержание молока у 7 телок было отрицательно коррелированным. По результатам геномной оценки 3 телки классифицированы как отличные, 3 - как умеренные и 4 - как слабые. Проведенные исследования по геномной оценке телок в ОАО «Нива» указывают на перспективность его использования в селекционно-племенной работе, поскольку дальнейшего ускоренного повышения эффективности молочного скотоводства без использования прогрессивных методов оценки ремонтного молодняка не будет. позволяют в короткие сроки повысить продуктивные, родственные и качественные показатели молочной продуктивности коров. В настоящее время 17 из 20 телок, прошедших геномную оценку, подтвердили результаты проведенных исследований.
Keywords: рк; скотоводство; импакт-фактор 2020; кларивате аналитикс; томсон; зарубежные авторы; зарубежное издание; голштинская порода скота; репродуктивность скота; геномная оценка